ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜ªð˜¯ð˜¤ð˜°ð˜¨ð˜¯ð˜ªð˜µð˜¢ E ð˜ð˜¶ð˜´ð˜¢ð˜³ð˜ªð˜¶ð˜® ð˜´ð˜°ð˜ð˜¢ð˜¯ð˜ª ð˜§. ð˜±ð˜ªð˜±ð˜¦ð˜³ð˜ª, ASSOCIADOS Ã€ MURCHA DA PIMENTEIRA-DO-REINO NA PARAÃBA - Lopes, Edson Batista; Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜ªð˜¯ð˜¤ð˜°ð˜¨ð˜¯ð˜ªð˜µð˜¢ E ð˜ð˜¶ð˜´ð˜¢ð˜³ð˜ªð˜¶ð˜® ð˜´ð˜°ð˜ð˜¢ð˜¯ð˜ª ð˜§. ð˜±ð˜ªð˜±ð˜¦ð˜³ð˜ª, ASSOCIADOS Ã€ MURCHA DA PIMENTEIRA-DO-REINO NA PARAÃBA